HUMAN RESOURCE INFORMATION SYSTEM : Fungsi, Peran, Manfaat, dan Penerapan Pada Wordpress - Hasna Nurfitriani Fatinah (Applied Business and Administration Journal, 2022)
In the era of globalization, information systems have a very important role in the company's activities in order to remain competitive in a competitive market. An information system is a component consisting of humans, technology, information and work procedures that process, store, analyze and disseminate information to achieve a goal. In a company or organization, one of the information systems that has an important role is the information system in the HR department or more commonly known as the Human Resource Information System (HRIS) which is a system used to collect, record, store, analyze and retrieve data related to HR in a company. Data collection can consist of salaries, compensation, leave, employee performance appraisals, employee benefits, pensions and many more. The purpose of this article will be to discuss the function of HRIS, the role of HRIS, and the benefits of HRIS in an organization or company. In addition, we will discuss the implementation of HRIS using a plugin found on WordPress which is easy for anyone to implement